Kinematic study of 1-cycle motion in elite 110 m hurdlers: Focusing on relations between running velocity, leg length and motion - Shibayama, K.; Fujii, N.; Ae, M. (Japan Journal of Physical Education, Health and Sport Sciences, 2011)
The purpose of this study was to investigate the kinematic characteristics of World and Japanese elite 110-m hurdlers during 1-cycle motion in relation to running velocity and leg length. Twenty-nine male hurdlers (SB: 12.92-14.37 s) participated. The motions from touchdown of the lead leg at the 6th hurdle (1st step) to touchdown of the takeoff leg at the 7th hurdle (4th step) were videotaped using a digital VTR camera (60 Hz), and two-dimensional coordinates were calculated based on calibration marks. The motions from touchdown of the takeoff leg at the 7th hurdle to touchdown of the lead leg at the 7th hurdle (1st step) were videotaped using two high-speed VTR cameras (200-300 Hz), and converted to two-dimensional coordinates after calculation of the three-dimensional coordinates using a DLT method. Kinematic parameters were calculated, including step length, step frequency, angles and angular velocities of the shank and thigh, and durations of the support and airborne phases. Stepwise multiple regression analysis was conducted with kinematic parameters as dependent variables, and with running velocity and leg length as independent variables at p<.05. The results were as follows: (1) Faster hurdlers achieved a higher step frequency with less range of thigh motion of the takeoff leg during the 2nd step. (2) The 3rd step played a role in adjusting the step length and preparing for hurdling, especially in hurdlers with a shorter leg length when preparing to increase the vertical GRF in the 4th step. (3) The allocation of time from takeoff at the 4th step to touchdown at the 2nd step was dependent on leg length. (4) Faster hurdlers achieved smaller vertical displacement of CG during the 1st step by shortening the support time to keep the position of the thigh perpendicular at the 2nd step. These results show that faster hurdlers achieved shorter durations of 1-cycle motion because of the increasing in horizontal CG velocity during the shorter support time at the 2nd step.